Biogeochemical cycling of gold: Transforming gold particles from arctic Finland - Reith, F.; Rea, M.A.D.; Sawley, P.; Zammit, C.M.; Nolze, Gert; Reith, T.; Rantanen, K.; Bissett, A. (Chemical Geology, 2018)
(Bio)geochemical cycling of gold (Au) has been demonstrated in present-day (semi)-arid, (sub)-tropical and temperate environment. Hereby biofilms on Au-bearing mineral- and Au-particle surfaces drive Au dispersion and reconcentration, thereby (trans)forming the particles. However, it is unknown if biogeochemical cycling of Au occurs in polar environments, where air temperatures can reach −40 °C and soils remain frozen for much of the year. Therefore, placer Au-particles, soils and waters were collected at two placer mining districts in arctic Finland, i.e., the Ivalojoki and Lemmenjoki goldfields. Sites were chosen based on contrasting settings ((glacio)-fluvial vs. glacial-till deposits) and depths (surface to 5m below current surface). Gold particles were studied using a combination of tagged 16S rRNA gene next generation sequencing and electron microscopic/microanalytical techniques. Across all sites a range of Au-particle morphologies were observed, including morphotypes indicative of Au dissolution and aggregation. Elevated Au concentrations indicative of Au mobility were detected in placer particle bearing soils at both districts. Typically Au-particles were coated by polymorphic biofilm layers composed of living and dead cells embedded in extracellular polymeric substances. Intermixed were biominerals, clays and iron-sulfides/oxides and abundant secondary Au morphotypes, i.e., nano-particles, microcrystals, sheet-like Au, branched Au networks and overgrowths and secondary rims. Biofilms communities were composed of Acidobacteria (18.3%), Bacteroidetes (15.1%) and Proteobacteria (47.1%), with β-Proteobacteria (19.5%) being the most abundant proteobacterial group. Functionally, biofilms were composed of taxa contributing to biofilm establishment, exopolymer production and nutrient cycling, abundant taxa capable of Au mobilization, detoxification and biomineralization, among them Cupriavidus metallidurans, Acinetobacter spp. and Pseudomonas spp., were detected. In conclusion, these results demonstrate that ...